How arguments are justified in the media debate on climate change in the USA and France. (2nd January 2015) - Yla–Anttila, Tuomas; Kukkonen, Anna
This paper examines the differences in the values that are evoked to justify arguments in the media debate on climate change in USA and France from 1997 to 2011. We find that climate change is more often discussed in terms of justice, democracy, and legal regulation in France, while monetary value plays a more important role as a justification for climate policy arguments in the USA. Technological and scientific arguments are more often made in France, and ecological arguments equally in both countries. We argue that understanding these national differences in argumentation at least partly as reflections of deep–seated cultural conceptions about what is worthy may help in understanding why disagreement persists in the global politics of climate change.